1896 R.I. Gen. Laws 371, tit. 14, ch. 110, § 1 - (:unkn) unknown (My University, 1896)
Every person who shall discharge any rifle, gun, musket, blunderbuss, fowling-piece, pistol, air-gun, spring-gun or other contrivance arranged to discharge shot, bullets, arrows, darts, or other missiles, in or across any road, street, square or lane shall be fined not less than three dollars nor more than twenty dollars.
Keywords: DISCHARGE